Emotions are social. - Parkinson, B (1996)
In this paper, I question the assumption that emotions are first and foremost individual reactions, and suggest instead that they are often best viewed as social phenomena. I show that many of the causes of emotions are interpersonally, institutionally or culturally defined; that emotions usually have consequences for other people; and that they serve interpersonal as well as cultural functions in everyday life. Furthermore, many cases of emotion are essentially communicative rather than internal and reactive phenomena. Previous research has often underestimated the importance of social factors in the causation and constitution of emotion. In conclusion, I recommend that existing cognitive and physiological approaches to emotional phenomena be supplemented or supplanted by social psychological analysis.